2008
DOI: 10.1183/09031936.00104108
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of tuberculosis in a low-incidence setting

Abstract: Recurrence of active tuberculosis following treatment of an initial disease episode can occur due to endogenous re-activation or exogenous re-infection.Cases of recurrent tuberculosis in the Australian state of New South Wales between 1994 and 2006 were identified by data linkage analysis with confirmatory review of case notes. Patients with more than one culture-positive disease episode during that time period who had completed treatment for the initial disease episode were included. Genotyping of Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 27 publications
7
36
0
Order By: Relevance
“…In New South Wales, Australia, an analysis of 3,731 culture-positive TB cases in the 1994-2006 period revealed that 15 (0.4%) patients had recurrent TB. Based on IS6110-RFLP typing, 11 (73%) cases were attributable to reactivation, and 4 (27%) were attributable to reinfection (482). Very similar data had previously been reported from The Netherlands, where 16% of all recurrent TB cases proved to result from reinfection on the basis of IS6110-RFLP typing (483).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isosupporting
confidence: 68%
“…In New South Wales, Australia, an analysis of 3,731 culture-positive TB cases in the 1994-2006 period revealed that 15 (0.4%) patients had recurrent TB. Based on IS6110-RFLP typing, 11 (73%) cases were attributable to reactivation, and 4 (27%) were attributable to reinfection (482). Very similar data had previously been reported from The Netherlands, where 16% of all recurrent TB cases proved to result from reinfection on the basis of IS6110-RFLP typing (483).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isosupporting
confidence: 68%
“…Regardless, without the M. tuberculosis genotyping results of both the initial and subsequent TB episode, the proportion of recurrent TB attributable to reinfection is rarely certain (11,12). In our earlier study of recurrent TB in the United States (22), we had genotyping results from both TB episodes for only 24 patients, similar to other previous studies of recurrent TB (9,(13)(14)(15)(17)(18)(19)(20)(21).…”
supporting
confidence: 59%
“…Among U.S.-born persons (n = 78; 57%), 30 (38%) were black non-Hispanic and 12 (15%) were Hispanic ( Table 1). Foreignborn persons with recurrent TB (n = 58; 43%) had immigrated a median of 12 years earlier at the time their second TB episode in the United States was diagnosed (interquartile range [IQR], [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Mexico was the most frequently reported country of origin of these immigrants (n = 19; 14%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In any model simplifying assumptions have to be made in order to develop a feasible model. The simplification that patients only develop active TB once (no recurrent episodes of TB) seems reasonable based on a study we conducted in a low incidence setting for TB that showed that the risk of TB recurrence (re-infection with a new TB strain or reactivation with the previous TB strain) was only 0.4% over 13 years [31]. However, this assumption limits the applicability of the decision aid to settings with a low incidence of TB, as the risk of recurrent TB via re-infection is substantial in settings with a high incidence of TB, and a previous course of treatment for LTBI does not protect a person from being re-infected.…”
Section: Discussionmentioning
confidence: 99%